2010
DOI: 10.2319/112409-665.1
|View full text |Cite
|
Sign up to set email alerts
|

Bone inductive proteins to enhance postorthodontic stability

Abstract: Objectives: To evaluate the use of bone morphogenetic proteins to enhance postorthodontic stability in sheep and to develop a biological method of postorthodontic retention. Materials and Methods: First incisors were extracted in four mature and healthy sheep, and the second incisors were tipped reciprocally toward the midline and then retained. Dried bone matrix was injected into the distal periodontal space of the left second incisor. The right second incisor was left as a control. Both incisors were retaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
24
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 17 publications
(14 reference statements)
5
24
0
Order By: Relevance
“…Moreover, the relapse rate in the CHA‐aPRF group was significantly lower than in the other groups, and this was associated with a significant decrease in osteoclast activity (TRAP‐positive cells), with a concomitant significant increase in osteoblast number. This finding indicates that differences in the appearance of osteoclast‐osteoblast may affect the relapse movement and this was in accordance with the results of Hassan et al The decreasing number of TRAP‐positive cells, indicates decreased resorption, and thus, decreased OTM. The use of TRAP as a marker for osteoclast activity has been well‐documented .…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, the relapse rate in the CHA‐aPRF group was significantly lower than in the other groups, and this was associated with a significant decrease in osteoclast activity (TRAP‐positive cells), with a concomitant significant increase in osteoblast number. This finding indicates that differences in the appearance of osteoclast‐osteoblast may affect the relapse movement and this was in accordance with the results of Hassan et al The decreasing number of TRAP‐positive cells, indicates decreased resorption, and thus, decreased OTM. The use of TRAP as a marker for osteoclast activity has been well‐documented .…”
Section: Discussionsupporting
confidence: 91%
“…This might suggest that PRP injection speeded the remodeling of the PDL and promoted new bone formation at a higher rate helping in faster stabilization of the new tooth position. These findings comes in accordance with Hassan AH, Al-Hubail A and Al-Fraidi AA (13) who injected bone morphogenic proteins (BMPs) Volume 51 -June 2017 around orthodontically moved teeth and Han G et al (12) after systemic administration of simvistatin following removal of orthodontic forces. Both (BMPs) and simvistatin are bone inductive materials.…”
Section: Discussionsupporting
confidence: 74%
“…This randomized controlled animal study was carried out to test the hypothesis that platelet rich plasma (PRP) can be used as a safe biological retainer to minimize or prevent tooth relapse following orthodontic tooth movement. The literature reported some successful attempts for biological control of relapse using pharmacological drugs (9)(10)(11)(12)(13)(14) . However, the use of PRP has superior advantages over any other pharmacological drug.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown the ability of BMPs to induce bone formation in a variety of models having many clinical applications in orthopaedics and oral and maxillofacial surgery (Geiger et al, 2003;Hassan et al, 2010;Herford & Boyne, 2008;Urist et al, 1984). Delivery systems for biosafe growth factors and biodegradable carriers have been used to achieve the slow, controlled release of growth factors at the site of implantation (Herford & Boyne, 2008).…”
Section: Introductionmentioning
confidence: 99%